The Translation of Idiomatic Expressions in the Karonese Cultural Legend “Pustaka Sembiring” into English - Helti Margaretha Tarigan; Syahron Lubis; T. Thyrhaya Zein (Talenta Publisher, 2021)
Abstract. This study is about the translation of idiomatic expressions in the Karonese cultural legend “Pustaka Sembiring” into English. An idiomatic expression is a combination of words that form figurative meanings, cannot be interpreted from the literal meaning of its forming words , and the meaning is bound to the context, so transferring meaning between two different cultures becomes a challenge for translators in implementing appropriate translation strategies. This research applied the descriptive qualitative method. The source of the research data was a legend entitled